Effects of total sleep deprivation on components of top‐down attentional control using a flexible attentional control task. (7th October 2022) - Stenson, Anthony R.; Whitney, Paul; Hinson, John M.; Hansen, Devon A.; Lawrence‐Sidebottom, Darian; Skeiky, Lillian; Riedy, Samantha M.; Kurinec, Courtney A.; Van Dongen, Hans P. A.
Summary: Sleep deprivation consistently decreases vigilant attention, which can lead to difficulty in performing a variety of cognitive tasks. However, sleep‐deprived individuals may be able to compensate for degraded vigilant attention by means of top‐down attentional control. We employed a novel task to measure the degree to which individuals overcome impairments in vigilant attention by using top‐down attentional control, the Flexible Attentional Control Task (FACT). The FACT is a two‐choice task that has trials with valid, invalid, and neutral cues, along with an unexpected switch in the probability of cue validity about halfway in the task. The task provides indices that isolate performance components reflecting vigilant attention and top‐down attentional control. Twelve healthy young adults completed an in‐laboratory study. After a baseline day, the subjects underwent 39 hours of total sleep deprivation (TSD), followed by a recovery day. The FACT was administered at 03:00, 11:00, and 19:00 during sleep deprivation (TSD condition) and at 11:00 and 19:00 after baseline sleep and at 11:00 after recovery sleep (rested condition). When rested, the subjects demonstrated both facilitation and interference effects on cued trials. While sleep deprived, the subjects showed vigilant attention deficits on neutral cue trials, and an impaired ability to reduce these deficits by using predictive contextual cues. Our results indicate that the FACT can dissociate vigilant attention from top‐down attentional control. Furthermore, they show that during sleep deprivation, contextual cues help individuals to compensate partially for impairments in vigilant attention, but the effectiveness of top‐down attentional control is diminished.